Solution-processed graphene oxide electrode for supercapacitors fabricated using low temperature thermal reduction. Issue 37 (9th June 2020) - Kil, Hye-Jun; Yun, Kayoung; Yoo, Mak-Eum; Kim, Seungchul; Park, Jin-Woo
Abstract : We present a low temperature and solution-based fabrication process for reduced graphene oxide (rGO) electrodes for electric double layer capacitors (EDLCs). Abstract : We present a low temperature and solution-based fabrication process for reduced graphene oxide (rGO) electrodes for electric double layer capacitors (EDLCs). Through the heat treatment at 180 °C between the spin coatings of graphene oxide (GO) solution, an electrode with loosely stacked GO sheets could be obtained, and the GO base coating was partially reduced. The thickness of the electrodes could be freely controlled as these electrodes were prepared without an additive as a spacer. The GO coating layers were then fully reduced to rGO at a relatively low temperature of 300 °C under ambient atmospheric conditions, not in any chemically reducing environment. Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) results showed that the changes in oxygen functional groups of GO occurred through the heat treatments at 180 and 300 °C, which clearly confirmed the reduction from GO to rGO in the proposed fabrication process at the low thermal reduction temperatures. The structural changes before and after the thermal reduction of GO to rGO analyzed using Molecular Dynamic (MD) simulation showed the same trends as those characterized using Raman spectroscopy and XPS. An EDLC composed of the low temperature reduced rGO-based electrodes and poly(vinyl alcohol)/phosphoric acid (PVA/H3 PO4 ) electrolyte gel was shown to have high specific capacitance of about 240 F g −1 together with excellent energy and power densities of about 33.3 W h kg −1 and 833.3 W kg −1, respectively. Furthermore, a series of multiple rGO-based EDLCs was shown to have fast charging and slow discharging properties that allowed them to light up a white light emitting diode (LED) for 30 min.